THE EFFECT OF BABY LED WEANING METHOD ON ORAL MOTOR SKILLS IN BABIES 6-12 MONTHS IN THE WORKING AREA OF THE EAST PEUREULAK PUSKESMAS - Rahmisyah Rahmisyah; Herna Linda; Sri Rizki Purnamita Jayati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT Oral motor skills for babies aged 6-12 months can be improved by providing stimulation such as baby-led weaning, which is a method of eating activities that introduces healthy family foods that are often consumed by families in the form of finger foods and gives children the opportunity to eat on their own from the start of the process of introducing complementary foods. breast milk. The aim of this research was to determine the effect of the baby-led weaning method on oral motor skills in babies 6-12 months in the UPTD Work Area of ​​the East Peureulak Health Center. The research design used in this research is quasi-experimental with a one group pretest-posttest approach. The population in this study were all 127 babies aged 6-12 months in the East Peureulak Health Center Working Area. The number of samples in this study was 15 babies 6-12 months. The sampling technique in this research used purposive sampling. Data analysis was carried out univariate and bivariate using the Wilcoxon test. The results of the study showed that the oral motor skills of babies aged 6-12 months before being given the baby led weaning method were 6.6 with a standard deviation of 0.737 and a Confidence Interval of 5-8 and after being given the baby led weaning method was 7.4 with a standard deviation of 0.516 and Confidence Intervals 7-8. There is an effect of baby-led weaning on oral motor skills in babies 6-12 months with a p-value of 0.004 (p<0.05). It is hoped that parents can use baby-led weaning as an option method for providing MPASI to stimulate children's motor skills, increase children's appetite, train children to recognize food textures, and must still be under the supervision of competent health workers.